Framing of the Covid-19 Infodemic on Topics and Tones of News Headlines in Indonesian and Malaysian Online Newspapers - Yuniawan, Tommi; Urip, Sri Rejeki; Istanti, Wati; Din, Wardatul Akmam (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2024)
During the COVID-19 pandemic, the mass media was critical in conveying information about public health concerns and initiatives by the government aimed at mitigating the pandemic. This study used content analysis to determine how the COVID-19 news was framed in Indonesian and Malaysian media published between January and March 2021. This study examined the Republika and The Star newspapers. According to the findings of the data analysis, the results of this research found five general topics in both newspapers: public health, government policy, economics, politics, and culture and religion. The Republika newspaper publishes the most articles on public health, whereas The Star newspaper publishes the most articles on government policy, economy, politics, culture, and religion. However, public health and government policy are more popular topics in both countries. Meanwhile, based on the two newspapers, there are five types of news tones: solutions, fears, impacts, suggestions, and conflicts. A fearful tone is prevalent in Republika news, while the other four news tones may be found in The Star. The high prevalence of news with a fearful tone in the Republika newspaper is due to the high death rate caused by COVID-19, as well as the emergence of a new variant of COVID-19, even though news in Malaysia is widely broadcast using a solution tone and positive messages to readers.